2022
DOI: 10.1155/2022/8451725
|View full text |Cite
|
Sign up to set email alerts
|

Subsurface Tectonic Inferences of the Adamawa Region of Cameroon from EMAG2 Magnetic Data

Abstract: The study area includes an area between 6° to 8°N and 11° to 15°E. Geologically, it belongs to Precambrian basement (granites, gneisses), Proterozoic, and Archean (volcanic) series, showing the main heat sources of Cameroon. The purpose of this study deals to analyze and interpret the EMAG2 magnetic data in the Adamawa area using various advanced processing techniques. Thus, the mapping and depth estimation of underground structures are realized. The analysis of aeromagnetic map of the reduction to equator (RT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 38 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…Njeudjand et al [42] showed that Cameroon has geothermal potential due to the presence of Precambrian basement, Proterozoic, and Archean volcanic series, which are 6 Geofluids the main heat sources of Cameroon. The study estimated the depth of underground structure using EMAG2 magnetic data and advanced processing techniques.…”
Section: Global and Regional Trends In Geothermal Energymentioning
confidence: 99%
“…Njeudjand et al [42] showed that Cameroon has geothermal potential due to the presence of Precambrian basement, Proterozoic, and Archean volcanic series, which are 6 Geofluids the main heat sources of Cameroon. The study estimated the depth of underground structure using EMAG2 magnetic data and advanced processing techniques.…”
Section: Global and Regional Trends In Geothermal Energymentioning
confidence: 99%